STUDI GOLPUT PADA PEMILIH PEMULA (KASUS PEMILUKADA GUBERNUR RIAU TAHUN 2013 DI KELURAHAN REJOSARI KECAMATAN TENAYAN RAYA) - Putri, Rindry Alfioty; ", M. Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Riau Province has conducted election of regional heads in 2013 to elect the Governor and the Vice Governor. However, the number of people who do not use their voting rights remain high, including the beginners. Most of the beginners prefer not to vote in the election activities because they are not congenial to the things related to the world of politics. There are 807 beginners who do abstention at the time of the election of Governor of Riau in 2013. The purpose of this research is to investigate the characteristics of the beginners who choose not to vote and the factors that influence the beginners not to vote at the election of the Riau Governor by using Rush and Althoff’s theory which explains the causes of abstention.This research uses a descriptive-quantitative approach. The result of this research is obtained by doing surveys and giving questionnaires which are later presented in the form of images. Based on the result of the research, it is known that the factors which affect the beginners in doing abstention in the election of Riau Governor is due the feeling of apathetic and disbelief from the beginners towards the government and the idea that the election is just a waste of time. The beginners are also cynical because they think that the candidate is not able to lead the region and they do not believe in government systems. In addition, the idea that the election is pointless and the right to vote can not influence government policy show the existence of the group of beginners who remote themselves from the election activities. Furthermore, the beginners also act anomie by believing that the candidates only give promises and the election does not bring any change for political survival and the region itself.Key Words: Beginners, Abstention, Attitude